Perception of the Quality of Life amidst HIV/Aids Positive Individuals in Tertiary Care Hospitals of Lahore - Umbreen Navied, Rubina Sarmad (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The Quality of life (QOL) as defined by WHO is that individual’s perception of their position in life in the context of the culture and value systems in which they live and in relation to their goals, expectations, standards and concerns. The intimacy about illness depends upon whether an individual relates and perceives that he or she has a good life, which would be worthwhile to review in relation to QOL. Aim: To determine the perception of QOL of people affected with HIV/AIDS. Methods: This was an exploratory research conducted by non-probability convenient sampling of 139 HIV/AIDS positive and registered cases at the Voluntary Counseling Testing Centers (VCT center’s) at Services and Jinnah hospitals, Lahore, in 6 months in 2019. The WHOQOL BREF Questionnaire was used for data collection. Data compilation and analysis was done through SPSS software. The interviews were taken with informed consent by the investigator. Results: In 139 cases of HIV/AIDS positive registered individuals mean age was 32.12±8.54, with 78.4% males and 21.6% females. Regarding their perception of current illness (intake of medicine other than HIV), only 19.4% claimed that they were ill. However when asked about their perception about self-health as many as 85.6% claimed that they were suffering from some illness. The remaining did not perceive their problem as illness. The response of the study participants towards their perception of quality of life (QOL) was considered to be good/ very good (33.1%) and poor/ very poor (53.9%). Whereas 12.9% thought it was neither poor nor good. The current illness and quality of life scores were not statistically significant in all domains, except social relationship domain. Conclusion: The perception of QOL of HIV/AIDS person needs to be explored, especially in Pakistan. It is necessary to determine and address all the associated aspects which affect the QOL of HIV/AIDS patients..